Effects of Emergency Department Analgesia on the Management Timeline and Clinical Outcomes of Acute Appendicitis - Evirgen, Suat; Ahun, Erhan (The European Research Journal, 2026)
Objective: This study aimed to evaluate the association between the administration of analgesics (Opioids or Nonsteroidal Anti-Inflammatory Drugs [NSAID]) after the initial examination in the emergency department and the diagnostic process of acute appendicitis, the timing of surgery, and postoperative complications in patients presenting with abdominal pain and suspected acute appendicitis. Methods: A total of 925 patients aged 18–65 years who underwent surgery for acute appendicitis between January 2020 and May 2025 were retrospectively reviewed. Two age- and sex-matched groups were formed: 98 patients who experienced a delay in surgical treatment (case group) and 98 patients who underwent surgery within 24 hours following diagnosis (control group). Delay in surgical treatment was defined as an interval exceeding 24 hours from the initial examination to surgery. Early analgesia was defined as the administration of parenteral analgesics after the initial examination. Group comparisons used Fisher’s exact test for categorical variables and t-test or Mann–Whitney U test as appropriate for continuous variables, with two-sided α=0.05. Results: The groups were similar with respect to demographic and clinical characteristics. The rates of early opioid use were 24.5% in the case group and 26.5% in the control group, with no significant difference between them (P=0.742). In contrast, early NSAID use was significantly higher in the case group (32.7% vs. 18.4%, P=0.021). The delayed-treatment group had markedly higher rates of perforation (28.6% vs. 12.2%, P=0.004) and postoperative abscess (14.3% vs. 4.1%, P=0.013). Conclusion: Early opioid analgesia was not associated with diagnostic delay or complications, suggesting it may be used safely in patients with acute appendicitis. In contrast, NSAID administration was associated with diagnostic delays, leading to postponed surgical intervention and higher complication rates. It is therefore advisable to avoid NSAID use, particularly in patients presenting with atypical abdominal pain.